Rancang Bangun Sistem Penilaian Otomatis Olahraga Taekwondo Berbasis Arduino - Arif Rahman Hasibuan; Ade Zulkarnain Hasibuan; Munjiat Setiani Asih (Journal of Information System Research (JOSH), 2022)
Taekwondo is an unarmed martial art that emphasizes kicks, straight punches, and dynamic leg movements. Currently, taekwondo matches, especially in the kyorugi type, apply an automatic judging system through the Protector and Scoring System (PSS). PSS was first used for international sporting events in 2012 at the London Olympics to avoid misjudgments due to human vision limitations. However, these devices are still costly, so alternative options are needed. Using an Arduino and a pressure sensor could be a more affordable alternative. Arduino and smartphones can be integrated as monitoring systems to make these devices a better choice for automated assessments. The test results show that this system can provide accurate assessment results. The points the athlete earns depend on the type of attack performed. A straight kick on the body armor earns two points, while a punch earns one point. The spinning kick earns four points with the provision of two points from automatic scoring and the addition of two point manually via smartphone. Taekwondo protective devices and smartphones can communicate up to a distance of 10 meters without any barriers between the devices.